In Silico Prediction and 3D Model Analysis of Potential Epitope of Heat Shock Protein-70 (HSP70) Gallus gallus as Candidate Biomarkers for Poultry Meat Quality Tests - Depamede, Sulaiman Ngongu; Indarsih, Budi; Wiryawan, I Ketut Gede; Tamzil, Muhammad Hasil; Maskur , . (Emerging Challenges in Agriculture and Food Science Vol. 5, 2022)
The main objective of this study was to investigate potential epitopes of heat shock protein-70 (HSP70) from the chicken (Gallus gallus). The epitopes are very important for designing a vaccine to produce antibodies against HSP70 which in turn can be used as biomarkers to study HSP70 expression. It has been reported elsewhere that there is a correlation between HSP70, reflecting the presence of stressors, and meat quality. Reduction in poultry meat quality can be as a result of physical, chemical and biological stressors before-, during-, and after broilers slaughtering. The success in exploring a potential biomarker of HSP70 therefore will be very helpful for the assessment of poultry meat quality. In this study, an in silico study of the HSP70 sequences of Gallus gallus were conducted to analyze the potential epitopes as biomarkers. The method used was a software-based method related to bioinformatics. From this study, two potential biomarker candidate peptides related to HSP70 were obtained, namely AILMGDKSENVQD, and ISWLDRNQMAEKEEYEHKQKELEK. A 3-dimensional model design is also produced from these epitopes. Further research is still needed to prove the potential of these two biomarkers in vivo.